Injectable keratin hydrogels as hemostatic and wound dressing materials. (12th May 2021) - Tang, Ao; Li, Ying; Yao, Yiqian; Yang, Xuexia; Cao, Zhangjun; Nie, Huali; Yang, Guang
Abstract : A protein-based injectable hydrogel was prepared in a convenient way and applied for biomedical applications as hemostatic and wound dressing materials. Abstract : Injectable hydrogels hold promise in biomedical applications due to their noninvasive administration procedure and capacity enabling the filling of irregularly shaped defects. Protein-based hydrogels provide features including good biocompatibility and inherent biofunction. However, challenges still remain to develop a protein-based injectable hydrogel in a convenient way due to the limited active groups in proteins. Keratins are a group of cysteine-rich structural proteins found abundantly in skin and skin appendages. In this work, we utilized keratin and the Au(iii ) salt to develop an injectable hydrogel based on the dynamic exchange between disulfide bonds (S–S) and gold(i )–thiolates (Au–S). Such a hydrogel could be prepared at the physiological pH and applied as an injectable hydrogel for biomedical applications including hemostatic and wound dressing materials. Our findings demonstrated that this keratin injectable hydrogel showed a good hemostatic effect in both tail amputation and liver injury models. Moreover, it was proved efficient as a drug loading carrier, and the deferoxamine-loaded hydrogel showed a desirable wound healing effect in a full-thickness excision wound model.